Increased numbers of nucleoli in a genome-wide RNAi screen reveal proteins that link the cell cycle to RNA polymerase I transcription - Ogawa, Lisa M. (Mol Biol Cell, 2021)
Nucleoli are dynamic nuclear condensates in eukaryotic cells that originate through ribosome biogenesis at loci that harbor the ribosomal DNA. These loci are known as nucleolar organizer regions (NORs), and there are 10 in a human diploid genome. While there are 10 NORs, however, the number of nucleoli observed in cells is variable. Furthermore, changes in number are associated with disease, with increased numbers and size common in aggressive cancers. In the near-diploid human breast epithelial cell line, MCF10A, the most frequently observed number of nucleoli is two to three per cell. Here, to identify novel regulators of ribosome biogenesis we used high-throughput quantitative imaging of MCF10A cells to identify proteins that, when depleted, increase the percentage of nuclei with ≥5 nucleoli. Unexpectedly, this unique screening approach led to identification of proteins associated with the cell cycle. Functional analysis on a subset of hits further revealed not only proteins required for progression through the S and G2/M phase, but also proteins required explicitly for the regulation of RNA polymerase I transcription and protein synthesis. Thus, results from this screen for increased nucleolar number highlight the significance of the nucleolus in human cell cycle regulation, linking RNA polymerase I transcription to cell cycle progression.